Insulin resistance, adipocyte biology, and thiazolidinediones: A review - (:unkn) unknown (My University, 2007)
Obesity is a well-recognized risk factor for the development of insulin resistance and the metabolic syndrome. Adipokines secreted from adipocytes play an important role in the pathogenesis of insulin resistance, hypertension, disorders of coagulation, dyslipidemia, and glucose abnormalities associated with insulin resistance or the metabolic syndrome. The selective ligands of the nuclear transcription factor PPARγ, Thiazolidinediones (TZDs), induce differentiation of preadipocytes to mature and more insulin sensitive adipocytes. This review summarizes adipocyte biology, the role of the adipokines in the pathogenesis of insulin resistance, and the effects of TZDs on insulin resistance and the metabolic disorders associated with it. © Mary Ann Liebert, Inc.